THE PRESENCE OF COMMERCIAL BANKS IN METAVERSE’S FINANCIAL ECOSYSTEM: OPPORTUNITIES AND RISKS - Raffi Hasta Anggara, Muhammad; Davie, M. Reihan; Margani, Mahanani; Aristyana D, Made Ayu; Aulia, Mahdiah (Journal of Central Banking Law and Institutions, 2022)
The metaverse has been widely discussed as it is believed will affect almost every sector, one of those is the financial sector. The financial sector developed in the metaverse will likely be based on decentralized finance and blockchain technology, the latter of which is the primary source of the development of cryptocurrency and stable coins. Other than cryptocurrency and stable coins, CBDC is also predicted to emerge as one of the payment instrument options used in the metaverse. The presence of these technologies has formed the unique financial ecosystem in metaverse, differentiating it from the existing ecosystem which is characterized as centralized and traditionalfinance. The recently developed Meta Fi has created the question of whether commercial banks, as one of the most important financial institutions in the current financial ecosystem, will be able to penetrate and keep its relevance in the Meta Fi. This research will attempt to answer this question by explaining Meta Fi, its characteristics, and how commercial banks could co-exist alongside blockchain-based service in Metaverse.